Dramske protagonistke in politika spola na odrih sveta - Toporišič, Tomaž (Jezik in slovstvo, 2022)
In our examination of the selected plays and tragedy, we have focused primarily on gender politics, and more specifically on the phenomenon of female protagonists on the world stage, which is the title of this year’s essay as a part of high-school exit exam in Slovene as the mother tongue. The theme was explored through a comparative analysis of four classics of drama and theatre from antiquity to the second half of the 20th century, focusing on a selection of themes that are still of concern today: the po-sition of women and gender equality in contemporary societies. The women dramatized in the selected plays are representatives of groups that, according to Julia Kristeva’s interpretation, are marginalised in the patriarchal symbolic order and are subjected to various forms of repression of femininity. The determination of biological sex in these plays repeatedly turns out to be socially constructed, as it is based on social norms and regulations. It is the violation of these rules that gives rise to the dramatur-gical strategies and gender politics of the plays from antiquity to the present day.
Keywords: dramatis personae; dramske osebe; female protagonist; feminist studies; feministične študije; gender politics; politika spola; represija feminilnosti; repression of feminity; ženska protagonistka